Increasing Interest in Inclusive Education in the Context of Action Plan for the Development and Enhancement of Special Education during the Fourteenth Five-Year Period in China: An Analysis of Baidu Index Data - Long, Hongmei; Wang, Meijie; Tan, Qinyi; Chen, Pan; Teng, Luyan (Journal of Education, Health and Sport, 2022)
Objective: Current evidence shows that public interest in inclusive education has been rising since the implementation of Action Plan for the development and enhancement of special education during the Fourteenth Five-Year period in China. The aim of this study was to quantify recent trends in public interest and related online search behavior for inclusive education in the context of this Action Plan. Methods: Baidu Index, a database of search engines with massive information, was employed. By searching for the keyword inclusive education, and using content analysis to understand the data information related to inclusive education. This study also extracted the search trend data of Chinese netizens on the related terms "Law on the Protection of Persons with Disabilities " and "Regulation on the Education of Persons with Disabilities" from January 1, 2022 to October 27, 2022. Finally, it compares the search trend of public search interests of inclusive education with related terms. Results: The public's interest in "inclusive education" and the related terms "Law on the Protection of Persons with Disabilities " and "Regulation on the Education of Persons with Disabilities" has been on the rise since the implementation of the Action Plan. The search trend reached its peak in February and May 2022, the valley in January 2022, and the search volume in other time periods tended to be stable. Conclusion: Baidu Index can understand the public's interest in inclusive education. The study shows that the rising search trend of inclusive education is closely related to the implementation of the Action Plan. The search volume of the "Law on the Protection of Persons with Disabilities " and "Regulation on the Education of Persons with Disabilities" is basically the same as that of "inclusive education", but the average search volume daily of "inclusive education" is slightly higher than that of "Regulation on the Education of Persons with Disabilities".